2020
DOI: 10.3390/pr8101227
|View full text |Cite
|
Sign up to set email alerts
|

Classification, Force Deformation Characteristics and Cooking Kinetics of Common Beans

Abstract: Post-harvest characteristics of common beans influences its classification, which significantly affects processing time and energy requirements. In this work, ten bean cultivars were classified as either easy-to-cook (ETC) or hard-to-cook (HTC) based on a traditional subjective finger pressing test and a scientific objective hardness test. The hardness study used seed coat rigidity to explain the structural deformation observed during cooking. The result shows that the average hardness of raw dry ETC and HTC b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Several research works on bean soaking by various researchers have shown that soaking beans prior to cooking reduces cooking time ( Chigwedere et al., 2019 ; Schoeninger et al., 2014 ; Carmona-García et al., 2007 ; Onwuka and Opara, 2006 ). This has been attributed to the fact that as beans are being soaked, there is increased hydration, which results in softening of the seed coat, which makes it easier for the water to penetrate through during cooking resulting in decreasing the cooking time ( Kwofie et al., 2020 ; Chigwedere et al., 2019 ; Wood, 2017 ). Other researchers have also reported that soaking accelerates chemical and physical reactions, such as solubilisation, starch gelatinization and polymerization, and protein denaturation during cooking and this subsequently results in reduction of cooking time ( Wainaina et al., 2021 ; Zamindar et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several research works on bean soaking by various researchers have shown that soaking beans prior to cooking reduces cooking time ( Chigwedere et al., 2019 ; Schoeninger et al., 2014 ; Carmona-García et al., 2007 ; Onwuka and Opara, 2006 ). This has been attributed to the fact that as beans are being soaked, there is increased hydration, which results in softening of the seed coat, which makes it easier for the water to penetrate through during cooking resulting in decreasing the cooking time ( Kwofie et al., 2020 ; Chigwedere et al., 2019 ; Wood, 2017 ). Other researchers have also reported that soaking accelerates chemical and physical reactions, such as solubilisation, starch gelatinization and polymerization, and protein denaturation during cooking and this subsequently results in reduction of cooking time ( Wainaina et al., 2021 ; Zamindar et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, some studies have found that NaCl soaking solutions result in increased cooking times, such as Ávila and colleagues' investigation of cowpea ( Ávila et al, 2015) and Kwofie and fellow investigators' study on common beans (Kwofie et al, 2020). Interestingly, Kwofie and colleagues even comment that the local communities in Malawi use NaCl to help soften beans (Kwofie et al, 2020).…”
Section: Impacts Of Elevation and Cooking Conditions On Cooking Timementioning
confidence: 99%
“…The investigators found a similar trend for horsegram, with reductions of about 13% for water only, 31% for NaCl, and 45% for NaHCO 3 compared to unsoaked, as well as in mothbean, with 20%, 50%, and 80% decreases in cooking time. Although some studies have found slight increases in cooking time or hardness when soaking in salt solutions with NaCl and/or potassium chloride (KCl) (Ávila et al, 2015; Kwofie et al, 2020), these same studies have found decreases in cooking time when using soaking solutions with NaHCO 3 (Ávila et al, 2015) and potassium carbonate (K 2 CO 3 ) (Kwofie et al, 2020). Some of these differences could be attributed to different study designs.…”
Section: Introductionmentioning
confidence: 99%
“…Kwofie et al [8] investigates the relationship between the classification and force deformation characteristics of common beans and the influence of bean softeners on cooking time. This work classified ten bean cultivars as either easy-to-cook (ETC) or hard-to-cook (HTC) based on a traditional subjective finger pressing test and a scientific objective hardness test.…”
Section: Food Processing Technologiesmentioning
confidence: 99%
“…This special issue consists of three sections, focusing on food storage and preservation technologies [1][2][3][4], food processing technologies [5][6][7][8], and the applications of advanced mathematical modeling and computer simulations [9][10][11]. We wish to acknowledge the expert contributions of all authors here.…”
mentioning
confidence: 99%